Comprehensive oral rehabilitation in a patient with diabetes mellitus: a surgical, periodontal, and prosthetic approach for the recovery of masticatory function and the prevention of malnutrition - Vargas-Pico, Anahí (2025)
This case report highlights the dental rehabilitation of a patient with controlled diabetes mellitus, emphasizing the importance of oral health in overall well-being. The treatment involved periodontal therapy, fixed and removable prostheses, and precision attachments to restore aesthetics and masticatory function. Significant improvements in oral health, function, and quality of life were achieved, along with stabilization of periodontal health after five months of follow-up. The case underscores the role of proper masticatory function in preventing malnutrition, especially in diabetic patients, where poorly controlled oral health can exacerbate systemic conditions. An interdisciplinary approach is critical in addressing both functional and aesthetic needs, improving both oral and systemic health outcomes for diabetic patients.